PSXIV-2 Late-Breaking: The effect of nicotinamide riboside on pork loin chop color stability – a pilot study. (5th December 2019) - Gonzalez, John M; Paulk, Chad; Dunmire, Kara; Houser, Terry; O'Quinn, Travis
Abstract: The objective of this pilot study was to examine the effect of oral supplementation of nicotinamide riboside chloride (NR) on pork loin chop color stability. Seven days prior to the beginning of the experiment, 10 finishing barrows (initial BW 111.9±1.6 kg) were assigned to individual pens that allowed ad libitum access to food and water. Barrows were randomly assigned to 1 of 2 NR treatments, 0 or 30 mg/kg daily of NR (ChromaDex, Irvine, CA) mixed in Karo syrup and administered by oral gavage. Barrows were administered their assigned treatment for 10 d, after which they were harvested under USDA inspection. Twenty-four hours postmortem, whole-boneless loins were fabricated, vacuum packaged, and aged for 10 d. Loins were cut into 3 chops immediately posterior to the spinalis dorsi, with chop 1 being used for day-0 metmyoglobin reducing ability (MRA) analysis, chop 2 being used for day-4 MRA and oxygen consumption rate (OCR) analyses, and chop 3 for 8-day objective/subjective color evaluation and MRA and OCR analyses. There were no Treatment × Day interactions for all objective and subjective color measurements (P > 0.77). Day of display affected all measures consistent with the discoloration of meat (P < 0.02), except L* value which was not affected (P = 0.14). Objective measures indicated NR chops had greater a*, greater surface oxymyoglobin, and less surface metmyoglobin formation over the 8-day display period (P < 0.01). Panelists indicated NR chops had less discoloration form over the entire 8-day display period (P < 0.01), but treatment did not affect OCR and MRA (P > 0.19). Feeding NR at the end of the finishing period may enhance visual pork loin chop color during simulated retail display; however, a larger study is needed to confirm this finding.